Fungsi dan Makna Perapian di Permukiman Desa Kalidesel, Wonosobo, Jawa Tengah - Hermawan (ARCHIHUMANUM, 2023)
Fireplaces for people in mountainous areas have several functions including those that function for cooking, heating and preserving agricultural products. One of the villages in the mountainous region is Kalidesel Village, Wonosobo, Central Java. The fireplace in the Kalidesel village consists of several elements including a furnace known as a pawon, a small wooden table known as dingklik, a seat known as jengkok, a cupboard for furniture known as an Anjab and a place to put agricultural products known as para. The fireplace is maintained by the community because it has meaning for people's lives. This research will reveal the meaning of a fireplace in the Kalidesel Village Settlement, Wonosobo, Central Java. The method used is descriptive method with observation and interview strategies. Observations were made on several houses in the village of Kalidesel that still maintain a fireplace. Interviews were conducted in several communities in the Kalidesel Village. The results of the study show the functional, social and symbolic meaning of the function of a fireplace in the Kalidesel Village Settlement. Functional meaning that arises in accordance with the function of the fireplace as a cooking tool. The function shows the ecological aspects of the use of wood fuel by using a repek system (how to extract wood without damaging the environment). The social meaning can be seen from the function of warming which is used as a means to strengthen brotherhood. Not only do you come from blood ties, but your neighbors become sedul due to frequent gatherings and encounters with a fireplace. The symbolic meaning of the hearth as a spiritual means. The fireplace is believed to be able to be an intermediary tool that can provide fortune. The meaning of a hearth for people's lives is the creation of comfort and peace in life.